Proteomics of Bordetella pertussis whole-cell and acellular vaccines - Möller, Jens; Kraner, Max; Burkovski, Andreas (BMC Research Notes, 2019)
Objectives: Bordetella pertussis is the etiological agent of whooping cough, a bacterial infection of especially children, which may be fatal without treatment. In frame of studies to investigate putative effects of vaccination on host-pathogen interaction and clonal distribution of strains, in addition to Corynebacterium diphtheriae and Clostridium tetani toxoid vaccines, also whole-cell and acellular pertussis vaccines were analyzed by mass spectrometry. Data description: LC-MS/MS spectra were generated and analyzed using B. pertussis genome data and proteins present in whole-cell and acellular pertussis vaccines were identified. Subcellular localization of proteins and presence of signal peptides was determined bioinformatically.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Bordetella; DTP vaccine; LC-MS/MS; Mass spectrometry; Pertussis; Vaccination; Whooping cough